SPECIFIC NATURE OF EVALUATIVE SPEECH ACTS - Prihodko, Ganna (Advanced Education, 2018)
The article discusses the issues connected with the analysis of appearance of the evaluation in the utterance. Particular attention is paid to the illocutionary and perlocutionary effect of evaluative speech acts. The speech act is viewed in the paper as the minimum unit of communication. The structure of the speech act includes four levels: locution, proposition, illocution and perlocution. In the evaluative speech acts semantic basis serves as the category of evaluation. Considering semantic and pragmatic properties of the object of our study, the author proposes to distinguish the following types of evaluative speech acts: 1) focus on the subject; 2) focus on the object. Among evaluative speech acts, oriented on the object, the author singles out proper evaluative speech acts (praise, condemnation) and emotional evaluation speech acts (admiration, anger, respect). This approach is based on the fact that evaluative verbs are direct representatives of illocutionary intention of evaluative speech acts. The author comes to the conclusion that the classification of evaluative speech acts can rely on semantic and pragmatic features of evaluative verbs.